Sobre la esfera de significación. Reflexiones en torno a la "Cuarta investigación" de E. Husserl - Dottori, Ariel O. (Nómadas. Critical Journal of Social and Juridical Science, 2012)
Husserl´s interest in this research is to establish and clarify a number of distinctions: first, the distinction between categorematic and syncategorematic expressions, closed and open and, secondly, between dependent and independent objects, independent of the sphere of the significance. Opposing modern grammar, which is constructed from psychology and others empirical disciplines, Husserl rescued the old idea of a general grammar and aprioristic because, unlike the previous one, that can show that there are laws that determine a priori possible forms of meaning.
Keywords: Significations; general grammar; science.